Spawning Period and Size at Sexual Maturity of Spider Conch, Lambislambis (L. 1758) (Gastropoda: Strombidae), in Selected Reef Areas of the Visayas, Central Philippines - Mazo, Analyn M.; Germano, Bernardita P.; Ilano, Anthony S. (Silliman Journal, 2022)
A study on spawning and size at sexual maturity of the economically important spider conch, Lambis lambis was done in the Visayas, Central Philippines (10º59'10.73"N 125º39'58.61"E) which is useful information for the sustainable management of the overexploited spider conch. Spawning period was determined using histological analysis of gonads and data on gonadosomatic indices, as well as observations of spawning in captivity. Size at sexual maturity was determined based on a scatterplot of gonadosomatic indices (GSI) against shell length and noting other characteristics such as the thickening of the shell and marginal digitations and development of the penis (male) or egg groove (female). Minimum legal size was conservatively estimated at 80 mm but an important consideration should be that the folds of the marginal digitations are thick and solid and the penis or egg groove are fully developed. Spawningtakes place year round usually 1-5 days around new moon and full moon with peak seasons during February-May and SeptemberOctober. As a management measure, closed season for collection of the species can be enforced during the peak spawning season to allow sexually mature individuals to reproduce prior to harvest.